National Council of Jewish Women, Washington, D.C., Office, records - National Council of Jewish Women. Washington, D.C., Office
Correspondence, memoranda, minutes, reports, legislation, notes, speeches, testimony, publications, newsletters, press releases, photographs, newspaper clippings, and other printed matter, chiefly 1944-1977, primarily reflecting the efforts of Olya Margolin as the council's Washington, D.C., representative from 1944 to 1978. Topics include the aged, child care, consumer issues, education, employment, economic assistance to foreign countries, food and nutrition, housing, immigration, Israel, Jewish life and culture, juvenile delinquency, national health insurance, social welfare, trade, and women's rights. Special concerns emerged in each decade, including nuclear warfare, European refugees, postwar price controls, and the establishment of the United Nations during the 1940s; the NCJW's Freedom Campaign against McCarthyism in the 1950s; civil rights and sex discrimination in the 1960s; and abortion, human rights, the Equal Rights Amendment, and Soviet Jewry in the 1970s.
Includes material on the Washington Institute on Public Affairs and the Joint Program Institute (both founded by a subcommittee of the Washington Office), on activities of various local and state NCJW sections, and on the Women's Joint Congressional Committee and Women in Community Service, two organizations that were founded in part by the National Council of Jewish Women.
Library of Congress Motion Picture, Broadcasting, and Recorded Sound Division.
Posters Library of Congress Prints and Photographs Division.
Established in 1944 as a liaison office between the National Council of Jewish Women and the U.S. Congress and government agencies; coordinated through the council's Public Affairs Department in New York, N.Y.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: McCarthy, Joseph, -- 1908-1957.; United Nations; United States. -- Congress; Women in Community Service (U.S.); Abortion; Older people; Anti-communist movements -- United States; Child care; Civil rights; Consumers; Commerce; Economic assistance; Education; Emigration and immigration; Equal rights amendments; Food; Housing; Human rights; Jews -- Social life and customs; Jews -- Soviet Union; Juvenile delinquency; Lobbying -- United States; National health insurance; Nuclear warfare; Nutrition; Sex discrimination; Social problems; Women -- Employment; Women's rights; World War, 1939-1945 -- Refugees; Israel; Margolin, Olya; Joint Program Institute; Washington Institute on Public Affairs; Women's Joint Congressional Committee (U.S.)